PENERAPAN METODE PLAY-BASED LEARNING UNTUK MENUMBUHKAN KARAKTER DAN KEMANDIRIAN PESERTA DIDIK DI MADRASAH IBTIDAIYAH NURUL MUN'IM PROBOLINGGO - St Romlah; Zaini Gunawan (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
This study addresses the application of the Play-Based Learning (PBL) method as an innovative strategy to foster character and independence in students at Madrasah Ibtidaiyah Nurul Mun'im Probolinggo. The main objective of this study is to describe the implementation of PBL and identify its impact on the development of character values ​​such as cooperation, honesty, discipline, and empathy. The method used is a qualitative case study approach, with data collection techniques through in-depth interviews with teachers, students, and parents, as well as participant observation and documentation. The results of the study indicate that the implementation of PBL through six systematic stages ranging from goal planning to reflection and appreciation has proven effective in transforming the role of teachers into educational facilitators capable of creating a safe and supportive learning ecosystem. A significant impact is seen in increasing students' self-confidence, responsibility, and problem-solving abilities that grow from intrinsic awareness, not just extrinsic compliance. The contribution of this study provides a theoretical and practical framework for the development of Islamic education in integrating Islamic values ​​and local wisdom into modern, adaptive learning methods. These findings are expected to serve as a reference for other primary education institutions to reform their character education strategies to be more dynamic, inclusive, and relevant.